Hubungan Sikap Kerja, Motivasi Dan Kepemimpinan dengan Kinerja Staf Pada Universitas Muhammadiyah Tangerang (UMT). Studi Kuantitatif Pada Program Studi Manajemen Universitas Muhammadiyah Prof. DR. HAMKA (UHAMKA). - Sugeng Siswondo (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
The aim of this research is for obtaining information whether there is connection among attitude to work, motivation and leadership to the performance of employees of UMT.The type of this research is explanatory research that explains the connection of attitude to word, motivations and leadership to the performance of the employees of UMT. The writer got the data by collecting the questioners. The writer uses double regression analysis in doing his analysis.The result of the research shows that there is connection among attitude to word, motivation and leadership to the employees of UMT, with the determination contribution (R2) 0,987 or 98,7%. It was explained by another variable exclude the concept of the research and the linear of regression with the result Y=56,033 +0,322 X1 + 0,119 X2 -0,210X3. The result of the research shows that motivation variable is more dominant in influencing the performance of the employees of UMT with the value 0,322 whereas the connection of attitude to word variable is 0,322 and the connection of leadership variable is -0,210.From the result of the research, the writer concludes that the performance of the employees of UMT is more increased if the attitude to word, motivation and leadership are better. Attitude to word can be improved by giving training about more qualified attitude to word. Motivation can be done by encouraging the employees to do innovative working, giving award to the best employee, making plan and setting the goal to be achieved by the foundation